2015
DOI: 10.1002/ana.24308
|View full text |Cite
|
Sign up to set email alerts
|

Retinal damage and vision loss in African American multiple sclerosis patients

Abstract: Objective To determine whether African-American (AA) multiple sclerosis (MS) patients exhibit more retinal damage and visual impairment compared to Caucasian-American (CA) MS patients. Methods 687 MS patients (81 AA) and 110 healthy control (HC) subjects (14 AA) were recruited at three academic hospitals between 2008 and 2012. Using mixed effects regression models, we compared high and low contrast visual acuity (HCVA and LCVA) and high-definition spectral-domain optical coherence tomography (Cirrus-OCT) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 40 publications
6
47
0
3
Order By: Relevance
“…In our study, the small regional differences within GM were compared, as opposed to entire tissue volumes, and importantly, our patients were less advanced in the disease process. A recent study utilizing optical coherence tomography demonstrated that AAwMS had a more rapid accumulation of retinal damage as compared to CAwMS . A study investigating 2 alleles that are highly associated with MS, namely, HLA‐DRB 1 and HLA‐DQB 1 , concluded that genetic loci embedded in these alleles are not only limited to disease susceptibility but also influence clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the small regional differences within GM were compared, as opposed to entire tissue volumes, and importantly, our patients were less advanced in the disease process. A recent study utilizing optical coherence tomography demonstrated that AAwMS had a more rapid accumulation of retinal damage as compared to CAwMS . A study investigating 2 alleles that are highly associated with MS, namely, HLA‐DRB 1 and HLA‐DQB 1 , concluded that genetic loci embedded in these alleles are not only limited to disease susceptibility but also influence clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study utilizing optical coherence tomography demonstrated that AAwMS had a more rapid accumulation of retinal damage as compared to CAwMS. 33 A study investigating 2 alleles that are highly associated with MS, namely, HLA-DRB 1 and HLA-DQB 1 , concluded that genetic loci embedded in these alleles are not only limited to disease susceptibility but also influence clinical outcomes. Interestingly, the study also indicated that African ancestry at the HLA locus independently correlated with disability and worsening disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to patient sampling within our RRMS cohort, we were unable to clarify if race or ethnicity alter treatment effects on rates of retinal atrophy over time. Larger, longitudinal studies in the future should address this since it has been proposed that African American patients with MS may have faster rates of retinal atrophy as compared to Caucasian American patients with MS. 32 Future studies should also aim to determine whether rates of retinal atrophy vary according to therapeutics in patients with progressive MS. Finally, this study did not include MRI-derived brain atrophy data, which would help to further corroborate our findings and to confirm that the effects of DMT classes on retinal atrophy similarly reflect their effects on brain atrophy.…”
Section: Comparison Of Rates Of Gcip Thinning Between Rrmsmentioning
confidence: 99%
“…However, contemporary studies are challenging the longheld belief that African Americans are at a reduced risk for developing multiple sclerosis (Wallin et al, 2012;Langer-Gould et al, 2013). Furthermore, compared with whites, African Americans are more likely to have a more severe disease course, which at least in part appears to be genetically determined (Buchanan et al, 2004;Cree et al, 2004Cree et al, , 2009Boster et al, 2009;Kimbrough et al, 2014). Here, we applied the ImmunoChip to a well-curated African American multiple sclerosis data set to investigate: (i) whether European multiple sclerosis-associated variants are also associated with the disease in African Americans; (ii) whether the smaller haplotype blocks, characteristic of African American genomes, can contribute to better mapping of the functionally relevant variants driving the association; and (iii) whether the array can identify novel multiple sclerosis-associated loci in African American patients.…”
Section: Introductionmentioning
confidence: 99%